Analisis Wisatawan Dan Pengaruhnya TerhadapPendapatan Pedagang Di Museum Sangiran KecamatanKalijambe Kabupaten Sragen - Kastuti, Sri; , Dr. H. Kuswaji Dwi Priyono, M.Si; , Dra. Hj. Retno Woro Kaeksi (2015)
ABSTRACT Sangiran Museum was one of the tour object in Sragen Regency, located in band of main road Solo - Purwodadi was easy reached. Research purpose to: 1) Analysing tourist characteristic on habit and red letter day, 2) Analysing merchant characteristic on habit and red letter day, 3) Analysing the correlation between amounts of tourist to merchant earnings. Method used in this research was survey method with primary data and secondary data analysis. Primary data collecting method use interview technique with respondents, while secondary data get obtained from related institution archives and the data analyse was used frequency and cross tabulation tables. Area research election use purposive sampling method and data was used in this research was primary and secondary data. Research shows that the Tourist Characteristics: a) tourist holiday paying a visit more coming from outside area (external Sragen), b) tourist habit paying a visit more coming from within area (Sragen), c) the majority of tourist education have Senior High School education of both for red letter day and also ordinary day, d) the majority of old age the tourist of 15 - 24 years old on red letter day and also ordinary day, e) the majority of marriage status tourist have unmarried status on red letter day and also ordinary day, f) the majority of tourist Gender was a man on red letter day and also ordinary day. WhileMerchant Characteristic: a) the majority of old age the merchant was 25 - 34 years old on red letter day and also ordinary day, b) the majority of merchant gender on habit was woman, c) the majority of merchant gender on holiday was a man d) the majority of merchant education was Senior High School on red letter day and also ordinary day that was on habit 56.2% while 50% on holiday. Amount of tourist paying a visit in Sangiran Museum tour object have an influence with the merchant earnings in Sangiran tour onject location.This matter was shown with chi square statistical test obtained χ2 count > χ2 table of hence can be interpreted that the relation between amount of earnings with many incoming tourist was significant and get coefficient contingensi (k) equal to 0,70 so that the relation between hand in glove variable. Keyword: Tourist Analyse, Merchant Earnings in Sangiran Museum of Kalijambe Distric Sragen Regency